Project Based Learning as an inclusive methodology: appropriation of English as a second language through social intervention schemes - Alvarez Idarraga, Nelly Johana (Rastros Rostros, 2021)
The objective of this article is to reveal the academic validity of the use of Project-Based Learning in the process of learning English as a foreign language. The approach that was used is mixed, and it was developed through a sequential explanatory study, the research sample is intentional, with 26 participants from second grade of primary school who were between 7 and 8 years old, 13 males, and 13 females, belonging entirely to middle and upper social class. As a result, the appropriation of English as a foreign language by establishing investigative spaces that involve the interests, the social reality, and the tangible affections of the learners is seen as an effective process. The research allows concluding that the use of Project-Based Learning strengthens the process of appropriation of English, as well as bases the implementation of social intervention schemes as components of pedagogical action.